Bis(4-carboxylpyrazol-1-yl)acetic acid: a scorpionate ligand for complexes with improved water solubility - Tzegai, Wintana; Reil, Michaela; Burzlaff, Nicolai (Dalton Transactions, 2022)
Bis(4-carboxylpyrazol-1-yl)acetic acid (H(3)bcpza) (2), obtained in a one-pot synthesis, contains carboxyl groups that differ in their pK(a) values. The ligand exhibits heteroscorpionate kappa(3)-N,N,O-coordination whereupon the peripheral carboxyl groups are not involved in metal binding. The corresponding carbonyl complexes [Mn(H(2)bcpza)(CO)(3)] (4), [Re(H(2)bcpza)(CO)(3)] (5) and [Ru(H(2)bcpza)Cl(CO)(2)] (6a/6b) are partially soluble in water but readily soluble in PBS buffer.
CRIS-Team WoS Importer:2022-05-06